The fall of Banco Esp?rito Santo : Holy Spirit or devil in disguise? - Shein, James B.; Hawbecker, Jason P. (London : Kellogg School of Management, 2016)
In 2014, after nearly 150 years as one of Portugal's most wealthy and powerful families, the Esp?rito Santo family completely lost control of its empire, which included Banco Esp?rito Santo, Portugal's largest bank by market capitalization and second-largest private-sector bank in terms of assets, along with stakes in numerous financial, non-financial, privately held, and publicly traded companies. During the European financial crisis of 2010 to 2014, many of the family's companies required capital investment. To avoid family equity dilution, the family's patriarch, Ricardo Esp?rito Santo Silva Salgado, engaged in a creative money-go-round structure whereby Banco Esp?rito Santo would legally raise short-term commercial paper with high interest rates and sell them to third parties that were partially owned by the Esp?rito Santo family. These third parties then would sell that paper back to the bank's retail clients as safe investments similar to Portuguese deposits. The plan failed, and the house of cards that was the Esp?rito Santo empire collapsed. Students will consider whether Salgado and the board of Banco Esp?rito Santo acted appropriately or if they failed their fiduciary duties to the non-family shareholders of the bank.
Originally published in Shein, J. B., & Hawbecker, J. P. (2016). The Fall of Banco Esp?rito Santo: Holy Spirit or Devil in Disguise? 5-116-004. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Espirito Santo family; Silva, Ricardo Espirito Santo; Banco Esp?rito Santo (1999-2014); Financial crises -- Great Britain -- 20th century